(untitled) (CIPEEX, 2026)
This project analyzes the use of gamification as a didactic-pedagogical strategy in teaching about Cerrado biodiversity, focusing on promoting environmental awareness among elementary school students. The objective is to determine how the use of educational games on the Wordwall platform can promote engagement and meaningful learning of content related to the biome. The methodology adopted is a qualitative approach, with bibliographic, documentary, and field research. Data collection will be conducted through questionnaires (open-ended and closed-ended) administered to 7th and 9th grade students and science teachers at a public school in Santa Rita do Novo Destino, Goiás, using pre- and post-tests to assess impact. The goal is to identify the main challenges faced in teaching biodiversity, select appropriate educational games, evaluate the effectiveness of gamification in the teaching-learning process, and theoretically support its application. Expected results include increased student engagement, improved teaching practices, and strengthening critical environmental education. It is concluded that gamification, when based on solid pedagogical principles, can represent an innovative tool for the formation of an active and civic ecological awareness.